DCE-MRI detected vascular permeability changes in the rat spinal cord do not explain shorter latency times for paresis after carbon ions relative to photons. (December 2021) - Bendinger, Alina L.; Welzel, Thomas; Huang, Lifi; Babushkina, Inna; Peschke, Peter; Debus, Jürgen; Glowa, Christin; Karger, Christian P.; Saager, Maria
Highlights: DCE-MRI alterations precede radiation-induced myelopathy in the rat spinal cord. Increased vascular permeability was found for both photons and carbon ions. Vascular permeability increased earlier and was more pronounced for photons. This indicates radiation-specific molecular mechanisms in the myelopathy development. Abstract: Background and purpose: Radiation-induced myelopathy, an irreversible complication occurring after a long symptom-free latency time, is preceded by a fixed sequence of magnetic resonance- (MR-) visible morphological alterations. Vascular degradation is assumed the main reason for radiation-induced myelopathy. We used dynamic contrast-enhanced (DCE-) MRI to identify different vascular changes after photon and carbon ion irradiation, which precede or coincide with morphological changes. Materials and methods: The cervical spinal cord of rats was irradiated with iso-effective photon or carbon ( 12 C-)ion doses. Afterwards, animals underwent frequent DCE-MR imaging until they developed symptomatic radiation-induced myelopathy (paresis II). Measurements were performed at certain time points: 1 month, 2 months, 3 months, 4 months, and 6 months after irradiation, and when animals showed morphological (such as edema/syrinx/contrast agent (CA) accumulation) or neurological alterations (such as, paresis I, and paresis II). DCE-MRI data was analyzed using the extended Toft's model. Results: Fit quality improved with gradual disintegration of the blood spinal cord barrier (BSCB) towards paresis II. Vascular permeability increased three months after photon irradiation, and rapidly escalated after animals showed MR-visible morphological changes until paresis II. After 12 C-ion irradiation, vascular permeability increased when animals showed morphological alterations and increased further until animals had paresis II. The volume transfer constant and the plasma volume showed no significant changes. Conclusion: Only after photon irradiation, DCE-MRI provides a temporal advantage in detecting early physiological signs in radiation-induced myelopathy compared to morphological MRI. As a generally lower level of vascular permeability after 12 C-ions led to an earlier development of paresis as compared to photons, we conclude that other mechanisms dominate the development of paresis II.